(untitled) (Agro Productividad, 2021)
Objective: To compare different bed planting systems: narrow beds (80 cm), wide beds (100 cm), and flat soil, on the growth and yield of wheat under conservation system. Design/methodology/approach: Treatments were established on a complete block design with three replicates; also, wheat crop was grown during five seasons. Treatments were as follow: A) wide beds (furrows at 100 cm), B) narrow beds (furrows at 80 cm) and C) flat soil. Response variables were dry weight of 50 stems, weight of 1000 grains, number of spikes (m2), harvest index and yield. Also, the relationship between relative yield and cold units and degree-days were measured. Results: Flat soil reach the highest dry weight of 50 stems, whereas narrow beds had the maximum number of spikes per m2. Yield was equal between flat soil and narrow beds. No differences were found in the harvest index (HI) among the evaluated treatments. When comparing results between years, dry weight of 50 stems increased and the HI index decreased, affecting negatively the yield. A negative association was found between chill hours and yield. Findings/conclusions: Despite yield was equal between flat soil and narrow beds, reduction on yields was mainly associated with of reduction in chill hours occurring in each season.